Proses dan Dasar-Dasar Pengembangan Organisasi pada Lembaga Pendidikan: Studi Kasus SDN 09 2x11 Kayutanam - Daviatul Fadlillah (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
In the era of globalization and technological advancement, educational institutions are required to adapt effectively to dynamic internal and external changes. This study aims to describe the organizational development process at SDN 09 2x11 Kayutanam based on modern organizational change theories proposed by Burnes (2017), Lewin (1947), and Passenheim (2010). This research employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation studies. Data were analyzed using Miles, Huberman, and Saldaña’s (2014) interactive model, consisting of data reduction, data display, and conclusion drawing, supported by triangulation for validation. The findings indicate that organizational development in the school occurred systematically through three main stages: unfreezing, change, and refreezing. The principal acted as a change agent, encouraging innovation, enhancing teacher participation, and strengthening a collaborative work culture. The success factors included participative leadership, effective communication, and strong commitment from school members, while challenges involved limited facilities, inadequate documentation, and resistance to change. Overall, the study highlights the importance of transformational leadership and adaptive organizational culture in ensuring sustainable development within primary education institutions.